The Digital Abutment Check: An Improvement of the Fully Digital Workflow - Sebastian Hinz; Daniel Ellmann; Christian Wegner; Wolfgang Bömicke; Tobias Bensel (Case Reports in Dentistry)
By using modern digitalization techniques, an existing denture can be digitized and aid the provision of a new implant-supported denture according to a fully digital workflow. This includes fully navigated implant surgery and results in an immediately provided prosthetic restoration. However, even with the current digital workflow, it is challenging to achieve a definitive prosthetic restoration in a single treatment session. In order to achieve a definitive denture in as few treatment sessions as possible, we have implemented the digital abutment test. This test modified the existing data set and determined the final restoration. In the present case, the preexisting maxillary removable complete denture was converted into a fixed immediate restoration using the fully digital workflow. The workflow is divided into two treatment phases, each with three treatment sessions, where part of the second phase involves an innovative digital abutment check. The illustrated case shows an effective use of current digital possibilities. Special attention was also paid to a minimally invasive course of therapy.